2022
DOI: 10.1007/s41109-022-00455-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development goals: conceptualization, communication and achievement synergies in a complex network framework

Abstract: In this work we use a network-based approach to investigate the complex system of interactions among the 17 Sustainable Development Goals (SDGs), that constitute the structure of the United Nations 2030 Agenda for a sustainable future. We construct a three-layer multiplex, in which SDGs represent nodes, and their connections in each layer are determined by similarity definitions based on conceptualization, communication, and achievement, respectively. In each layer of the multiplex, we investigate the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The sustainable development goals are a set of 17 global goals set by the United Nations in 2015 and recently adopted in the 2030 agenda ( 1–5 ). The goals provide a “shared blueprint for peace and prosperity for people and the planet, now and into the future.” The goals cover a wide range of issues, including poverty, hunger, health, education, climate change, gender equality, water, sanitation, energy, the environment, and social justice ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sustainable development goals are a set of 17 global goals set by the United Nations in 2015 and recently adopted in the 2030 agenda ( 1–5 ). The goals provide a “shared blueprint for peace and prosperity for people and the planet, now and into the future.” The goals cover a wide range of issues, including poverty, hunger, health, education, climate change, gender equality, water, sanitation, energy, the environment, and social justice ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two main research gaps must be filled to efficiently use OSNs for sustainability awareness and advance the state-of-the-art in this body of knowledge. First, in the literature, scholars have explored how different factors, tools and approaches affect the success of sustainability awareness through OSNs (Chou and Huang, 2021;Sysoieva and Osadcha, 2020); proposed new methods, theoretical frameworks and approaches (Vasseur et al, 2022;Al-Marghilani, 2022); and showed different case examples (Bellantuono et al, 2022;Hurajova et al, 2022). The contributions of these studies should be considered in designing and developing OSNs and sustainability initiatives using OSNs.…”
Section: Introductionmentioning
confidence: 99%
“…First, in the literature, scholars have explored how different factors, tools and approaches affect the success of sustainability awareness through OSNs (Chou and Huang, 2021; Sysoieva and Osadcha, 2020); proposed new methods, theoretical frameworks and approaches (Vasseur et al. , 2022; Al-Marghilani, 2022); and showed different case examples (Bellantuono et al. , 2022; Hurajova et al.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the robustness of our analysis, we will employ the tool of complex networks (Newman, 2018 ), that is increasingly used, also in its recent formal developments (Bianconi, 2018 ; Amoroso et al, 2020 , 2021b ), along with or in replacement of traditional statistical techniques to unveil hidden information in many sectors of science and society, such as neuroscience (Sporns, 2011 ; Amoroso et al, 2018 , 2019 ; Bellantuono et al, 2021 ), genetics (Monaco et al, 2019 , 2020 ), economics (Hidalgo et al, 2007 ; Battiston et al, 2012 ; Tacchella et al, 2012 ; Hausmann et al, 2014 ; Bardoscia et al, 2017 , 2021 ; Pugliese et al, 2019 ; Amoroso et al, 2021a ), human mobility (Alessandretti et al, 2018 ), social and development-related issues (Bellantuono et al, 2020 , 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%